IPMomics: from genomics to extension for integrated pest management of cowpea: Proceedings of the 5th World Cowpea Research Conference, held at Palm Beach Hotel, Saly, Senegal. 27 September 1 October - Agunbiade, T.A.; Steele, L.; Coates, B.; Gassmann, A.; Margam, V.; Ba, M.; Dabiré, C.; Baoua, I.; Bello-Bravo, Julia; Seufferheld, F.; Sun, W.; Tamò, Manuele; et al. (2012)
Insect pests often develop resistance to insecticides, and such resistance represents a serious management problem. Devising methods that concurrently delay resistance and minimize injury by insects to field crops and stored grain has long been a goal of Integrated Pest Management (IPM). A centerpiece of IPM has been the combined use of biological control agents and prudent application of chemical insecticides. Unfortunately, successful application of IPM has remained a challenge. This chapter describes the use of emerging genomic technologies that may lead to a “systems” perspective of IPM for the control of pests of cowpea and other crops. This emerging field, which we refer to as “IPM-omics”, builds upon recent advances in genome sequencing technologies and detection of largescale gene polymorphisms, which are becoming economically feasible for pest insect systems. IPM-omics will also need to involve the use of information and communications technologies both to collect critical information on pest populations and to deploy practical IPM solutions. The information obtained on the temporal fluctuations, spatial distribution, and ecological diversification within target, non-target, and natural enemy populations can be overlaid on a geographic information systems (GIS) map to predict pest outbreaks and to decide how to apply control measures. The “systems” perspective of organism communities provided through IPM-omics may also facilitate the effective evaluation, modification, and optimization of IPM strategies. However, any resultant IPM program for crop pests will also require that extension agents, government agencies, and non-governmental organizations (NGOs) have the ability to easily access and deploy the IPM research findings through information and communications technologies. Thus, we also outline the need for an online system that facilitates the sharing and peer review of practical IPM outputs. Many of these tools are currently being developed to help farmers manage insect pests of cowpea in West Africa.